Students readiness and motivation to use mobile phone for learning english at higher learning institution - Mizad, Meizareena; Yusoff, Zailin Shah; Sayadi, Zainal Abidin; Abdul Latif, Azmi; Sukiman, Safra Liyana (AESS Publications, 2018)
The rapid growth on ICT have reshaped our live today, and nowadays' university students in Higher Learning Institutions have an immense use of mobile phones, iPads and other portable devices. Mobile learning or m-Learning focuses on the mobility of the learner while interacting with portable technologies. The use of mobile learning among university students is seen as an alternative to increase their interest and motivation on learning the academic programmes at Higher Learning Institution. The m-learners use mobile device for educational purpose at their own time convenience. An online questionnaire survey will be used to collect data for this study. The findings will reveal on the students‟ readiness which are basic readiness, skills readiness, psychological readiness and budget readiness at a public university in Malaysia in relation to mobile learning. The study will also explore the students‟ motivation towards the use of mobile technologies for learning English in the university. A discussion on the implications of the findings will also be presented.